Evidence for troponin C (TNNC1) as a gene for autosomal recessive restrictive cardiomyopathy with fatal outcome in infancy. Issue 12 (8th September 2016) - Ploski, Rafal; Rydzanicz, Malgorzata; Ksiazczyk, Tomasz M.; Franaszczyk, Maria; Pollak, Agnieszka; Kosinska, Joanna; Michalak, Ewa; Stawinski, Piotr; Ziolkowska, Lidia; Bilinska, Zofia T.; Werner, Bozena
Abstract : Restrictive cardiomyopathy is a rare form of pediatric cardiac disease, for which the known genes include MYH7, TNNT2, TNNI3, ACTC1, and DES . We describe a pediatric proband with fatal restrictive cardiomyopathy associated with septal hypertrophy and compound heterozygosity for TNNC1 mutations (NM_003280: p.A8V [c.C23T] and p.D145E [c.C435A]). This association between restrictive cardiomyopathy and TNNC1 mutations was strengthened by prospective observations on the second pregnancy in the family which revealed, in the presence of the same TNNC1 genotype, prenatally diagnosed hypertrophic cardiomyopathy which evolved into restrictive cardiomyopathy, heart failure and death at the age of 9 months. Contrary to previous reports, family and population analyses showed that each of the TNNC1 variants was not pathogenic when present alone. Our results (i) confirm that genetic backgrounds of hypertrophic cardiomyopathy and restrictive cardiomyopathy overlap and (ii) indicate that TNNC1 is a likely novel gene for autosomal recessive restrictive cardiomyopathy. © 2016 Wiley Periodicals, Inc.